Disorder of Sexual Development Males With XYY in Blood Have Exactly X/XY/XYY Mosaicism in Gonad Tissues - Yang, Yongjia; Chen, Fang; Luo, Zhenqing; Zheng, Yu; Zheng, Jiayong; Fu, Yuyan; Chen, Weijian; Luo, Haiyan (Frontiers in Genetics, 2021)
Y chromosome represents masculinization. The extra Y chromosome of XYY patients usually leads to overmasculinization phenotypes. The occurrence of several DSD cases with XYY in blood is controversial. Is XYY associated with disorder of sexual development (DSD)? What is the mechanism behind DSD in males with XYY in blood? To this end, this study retrospectively analyzed blood-karyotype data of 4437 DSD male children and karyotypes data of 6259 newborn males as the control. Exome sequencing was performed to test whether the patients with DSD and with XYY in blood had other variants on known DSD-genes. Testicular biopsy was performed. Fluorescence in situ hybridization (FISH) was used to test whether a sex chromosome mosaicism was present in the oral epithelial cells or gonad tissue of patients with DSD and with XYY in blood. Among 4437 DSD males who received cytogenetic evaluation, 14 patients with 47,XYY were identified. By contrast, five individuals among the 6259 controls had 47,XYY. XYY in blood is more frequent among males with DSD than in other males (p=0.004). The XYY karyotypes were confirmed again by GTG-banding in blood samples and by FISH performed on oral epithelial cells. Exome sequencing on seven XYY DSD patients was successfully performed, but results did not identify any pathogenic variant on 55 known DSD genes. Gonad biopsy (n=3) revealed testicular dysplasia and true hermaphroditism. FISH of gonad tissues (n=3) showed that all of the samples had mosaic for X/ XY/ XYY. This study is the first to investigate the relationship between XYY in blood and DSD. The knowledge that XYY is in the blood and in oral cells have X/XY/XYY mosaicism in gonadal tissue is new for both researchers and clinicians who seek to understand the genetic basis of DSD males.